Investigating the role of media in the identity construction of ethnic minority language speakers in Botswana : an exploratory study of the Bakalanga - Thothe, Oesi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2015)
This dissertation investigates the role of media in the identity construction of minority language speakers in Botswana, with a focus on the Bakalanga. The study is informed by debates around the degree to which the media can be seen to play a central role in the way the Bakalanga define their own identity. As part of this, it considers how such individuals understand their own sense of identity to be located within processes of nation-building, and in particular in relation to the construction of a national identity. It focuses, more particularly, on the extent to which the absence of particular languages within media can be said to impact on such processes of identity formation. The study responds, at the same time, to the argument that people's more general lived experiences and their broader social environment have a bearing on how they make sense of the media. As such, it can be seen to critique the assumption that the media necessarily play a central and defining role within processes of socialisation. In order to explore the significance of these debates for a study of the Bakalanga, the dissertation includes a contextual discussion of language policy in Botswana, the impact of colonial history on such policy and the implications that this has had for the linguistic identity of the media. It also reviews theoretical debates that help to make sense of the role that the media plays within the processes through which minority language speakers construct their own identity. Finally, it includes an empirical case study, consisting of qualitative interviews with individuals who identify themselves as Bakalanga. It is argued that, because of the absence of their own language from the media, the respondents do not describe the media as central to their own processes of identity formation. At the same time, the respondents recognise the importance of the media within society, and are preoccupied with their own marginalisation from the media. The study explores the way the respondents make sense of such marginalisation, as demonstrated by their attempts to seek alternative media platforms in which they can find recognition of their own language and social experience. The study thus reaffirms the significance of media in society "“ even for people who feel that they are not recognised within such media.
Keywords: Linguistic minorities -- Botswana; Kalanga language (Botswana and Zimbabwe); Kalanga (African people) -- Ethnic identity; Language policy -- Botswana; Mass media and language -- Botswana; Mass media and ethnic relations -- Botswana; Mass media -- Audiences; Mass media -- Social aspects -- Botswana